Neuroimaging in Clinical Trials for Huntington’s Disease: Emerging Research Findings: The Advancement Directions and Implications - Vinod B Bhamare; Sandip S Patil (International Journal of Brain Sciences, 2025)
Neuroimaging is very important in coordinating and conducting Huntington’s disease clinical trials as a tool in selecting patients, managing safety concerns, and assessing the benefits of interventions. This review presents the current uses and potential future uses of structural and functional magnetic resonance imaging (MRI), diffusion imaging, positron emission tomography (PET), proton magnetic resonance spectroscopy (MRS), perfusion imaging, and magneto encephalography (MEG) in HD trials. We describe how these modalities contribute to patient selection, biomarker optimization, and pharmacokinetic studies, as well as documenting disease amelioration and neuroplastic changes after treatment. Furthermore, they explore the difficulties of adapting neuroimaging approaches from research to clinical settings in relation to technical standardization, patient burden, costs for equipment, and difficulties of data interpretation. By critiquing, we identify novel developments in neuroimaging methods and discuss ways to enhance their application in HD trials. The review closes by highlighting the role of neuroimaging, in general, to improve patient prognosis and boost research in HD therapeutic interventions if implemented with precise modalities and research study designs. Huntington’s disease (HD), Neuroimaging/clinical research, Drug trials, Magnetic resonance imaging (MRI), Positron emission tomography (PET), Magnetoencephalography (MEG), Patient subgrouping/characterization, Disease prevention and brain reorganization.
Keywords: Brain reorganization; Disease modification; Huntington’s disease (HD); Patient stratification; Positron emission tomography (PET); clinical trials; magnetic resonance imaging (MRI); magnetoencephalography (MEG); neuroimaging